Quantitative assessment of brown adipose tissue metabolic activity and volume using (18)F-FDG PET/CT and β3-adrenergic receptor activation - Mirbolooki, M Reza (Springer, 2011)
BACKGROUND: Brown adipose tissue [BAT] metabolism in vivo is vital for the development of novel strategies in combating obesity and diabetes. Currently, BAT is activated at low temperatures and measured using 2-deoxy-2-(18)F-fluoro-D-glucose [(18)F-FDG] positron-emission tomography [PET]. We report the use of β3-adrenergic receptor-mediated activation of BAT at ambient temperatures using (R, R)-5-[2-[2,3-(3-chlorphenyl)-2-hydroxyethyl-amino]propyl]-1,3-benzodioxole-2,2-dicarboxylate, disodium salt [CL316,243] (a selective β3-adrenoceptor agonist) and measured by (18)F-FDG PET/computed tomography [CT]. METHODS: Control and CL316,243-treated (2 mg/kg) male Sprague-Dawley rats were administered with (18)F-FDG for PET/CT studies and were compared to animals at cold temperatures. Receptor-blocking experiments were carried out using propranolol (5 mg/kg). Dose effects of CL316,243 were studied by injecting 0.1 to 1 mg/kg 30 min prior to (18)F-FDG administration. Imaging results were confirmed by autoradiography, and histology was done to confirm BAT activation. RESULTS: CL316,243-activated interscapular BAT [IBAT], cervical, periaortic, and intercostal BATs were clearly visualized by PET. (18)F-FDG uptake of IBAT was increased 12-fold by CL316,243 vs. 1.1-fold by cold exposure when compared to controls. (18)F-FDG uptake of the CL-activated IBAT was reduced by 96.0% using intraperitoneal administration of propranolol. Average (18)F-FDG uptake of IBAT increased 3.6-, 3.5-, and 7.6-fold by doses of 0.1, 0.5, and 1 mg/kg CL, respectively. Ex vivo (18)F-FDG autoradiography and histology of transverse sections of IBAT confirmed intense uptake in the CL-activated group and activated IBAT visualized by PET. CONCLUSION: Our study indicated that BAT metabolic activity could be evaluated by (18)F-FDG PET using CL316,243 at ambient temperature in the rodent model. This provides a feasible and reliable method to study BAT metabolism.